Water-Based Synthesis and Enhanced CO2 Capture Performance of Perfluorinated Cerium-Based Metal–Organic Frameworks with UiO-66 and MIL-140 Topology - Mariolino Carta (ACS Sustainable Chemistry & Engineering, 2018)
Reaction of cerium ammonium nitrate and tetrafluoroterephthalic acid in water afforded two new metal–organic frameworks with UiO-66 [F4_UiO-66(Ce)] and MIL-140 [F4_MIL-140A(Ce)] topologies. The two compounds can be obtained in the same experimental conditions, just by varying the amount of acetic acid used as crystallization modulator in the synthesis. Both F4_UiO-66(Ce) and F4_MIL-140A(Ce) feature pores with size <8 Å, which classifies them as ultramicroporous. Combination of X-ray photoelectron spectroscopy and magnetic susceptibility measurements revealed that both compounds contain a small amount of Ce(III), which is preferentially accumulated near the surface of the crystallites. The CO2 sorption properties of F4_UiO-66(Ce) and F4_MIL-140A(Ce) were investigated, finding that they perform better than their Zr-based analogues. F4_MIL-140A(Ce) displays an unusual S-shaped isotherm with steep uptake increase at pressure <0.2 bar at 298 K. This makes F4_MIL-140A(Ce) exceptionally selective for CO2 over N2: the calculated selectivity, according to the ideal adsorbed solution theory for a 0.15:0.85 mixture at 1 bar and 293 K, is higher than 1900, among the highest ever reported for metal–organic frameworks. The calculated isosteric heat of CO2 adsorption is in the range of 38–40 kJ mol–1, indicating a strong physisorptive character.